PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 12 PADANG - Marhen, Heru; Zulfaneti, Zulfaneti; Harisman, Yulyanti (Pendidikan Matematika, 2013)
Understanding of concepts and skills students learning activities are essential to reach the goal of learning. So, we need the learning process afectifly and efficiently. It have influenced for students result. This research has goal to see the influence of implementation learning strategic of cooperative learning type Students Team Achievement Division (STAD) to the understanding of mathematical concepts and skills students learning activities. The type of research is experimental research. Technique of random sampling. The instrument used is the observation sheet student learning activities, with the activity types of Oral Activities, Writing Activities, and Mental Activities. Test student understanding of mathematical concepts experimental class was 87,15 with a standar deviation of 11,4 and 81,6 with the control class is standart deviation 14,4. Hypothesis testing using t-test of the one part, obtained t cound > t table is 1,69 > 1,645 this means the hypothesis is accepted. Conclusion is students understanding of mathematical concept by implementation learning strategic of cooperative learning type STAD better than the students understanding by applying conventional learning.